Unravelling the role of obesity and lipids during tumor progression - Zhao, Junzhe; Lee, Keene; Toh, Han Chong; Lam, Kong Peng; Neo, Shi Yong (Frontiers in Pharmacology, 2023)
The dysregulation of biochemical pathways in cancer promotes oncogenic transformations and metastatic potential. Recent studies had shed light on how obesity and altered lipid metabolism could be a driving force for tumor progression. Here, in this review, we focus on liver cancer and discuss how obesity and lipid-driven metabolic reprogramming affect tumor, immune and stroma cells in the tumor microenvironment and in turn, how alterations in these cells synergize to influence and contribute to tumor growth and dissemination. With increasing evidence on how obesity exacerbate inflammation and immune tolerance, we also touch upon the impact of obesity and altered lipid metabolism on tumor immune escape.